Vessel-Selective 4D-MRA Using Superselective Pseudocontinuous Arterial Spin-Labeling with Keyhole and View-Sharing for Visualizing Intracranial Dural AVFs - Togao, O.; Obara, M.; Kikuchi, K.; Helle, M.; Arimura, K.; Nishimura, A.; Wada, T.; Murazaki, H.; Van Cauteren, M.; Hiwatashi, A.; Ishigami, K. (American Journal of Neuroradiology, 2022)
BACKGROUND AND PURPOSE: An accurate assessment of the hemodynamics of an intracranial dural AVF is necessary for treatment planning. We aimed to investigate the utility of 4D-MRA based on superselective pseudocontinuous arterial spin-labeling with CENTRA-keyhole and view-sharing (4D-S-PACK) for the vessel-selective visualization of intracranial dural AVFs.MATERIALS AND METHODS: We retrospectively analyzed the images of 21 patients (12 men and 9 women; mean age, 62.2 [SD,19.2] years) with intracranial dural AVFs, each of whom was imaged with DSA, 4D-S-PACK, and nonselective 4D-MRA based on pseudocontinuous arterial spin-labeling combined with CENTRA-keyhole and view-sharing (4D-PACK). The shunt location, venous drainage patterns, feeding artery identification, and Borden classification were evaluated by 2 observers using both MRA methods on separate occasions. Vessel selectivity was evaluated on 4D-S-PACK.RESULTS: Shunt locations were correctly evaluated in all 21 patients by both observers on both MRA methods. With 4D-S-PACK, observers 1 and 2 detected 76 (80.0%, P < .001) and 73 (76.8%, P < .001) feeding arteries of the 95 feeding arteries identified on DSA but only 39 (41.1%) and 46 (48.4%) feeding arteries with nonselective 4D-PACK, respectively. Both observers correctly identified 10 of the 11 patients with cortical venous reflux confirmed by DSA with both 4D-S-PACK and 4D-PACK (sensitivity = 90.9%, specificity = 90.9% for each method), and they made accurate Borden classifications in 20 of the 21 patients (95.2%) on both MRA methods. Of the 84 vessel territories examined, vessel selectivity was graded 3 or 4 in 73 (91.2%) and 66 (88.0%) territories by observers 1 and 2, respectively.CONCLUSIONS: 4D-S-PACK is useful for the identification of feeding arteries and accurate classifications of intracranial dural AVFs and can be a useful noninvasive clinical tool.ASLarterial spin-labelingCNRcontrast-to-noise ratioCVRcortical venous reflux4D-PACK4D-MRA based on pseudocontinuous arterial spin-labeling combined with CENTRA-keyhole and view-sharing4D-S-PACK4D-MRA based on superselective pseudocontinuous arterial spin-labeling with CENTRA-keyhole and view-sharingDAVFdural AVFECAexternal carotid arterypCASLpseudocontinuous arterial spin-labeling